Scopolamine exerted antidepressant-like behavioral effects via restoring the synaptic plasticity in CRS-treated mice - Peng-Wei Bi; Si-Rui Sun; Jia-Ning Zhao; Hui-Ying Zhang; Ze Lv; Yong-Yu Yin; Yun-Feng Li (Metabolic Brain Disease, 2025)

7,8-Dihydroxyflavone ameliorates bone loss by regulating TRKB/AKT/FOXO3a pathway in a mouse model of alzheimer’s disease - Dong Liu; Xiaoxiong Li; Peng Shi; Wenjuan Hong; Jie Huang; Mingliang Hou; Linqiu Ma; Qirong Liao; Hongyan Yang; Xiaoyan Fu; Huadong Zhou; Jing Lu; et al. (Psychopharmacology, 2025)

Global phylogenomic insights into the evolutionary adaptation of Helicobacter pylori: evidence from 1467 isolates and the fixation of cage D792 mutation - Shenke Zhang; Lianghui Peng; Boyu Liao; Cuixian Yang; Jingjie Song; Zeeshan Umar; Shengli Zhang; Liqiu Ma; Rui Liu (Genome Instability & Disease, 2025)

Monitoring and determinants analysis of canopy layer urban heat island in China based on both air temperature and apparent temperature - Yuanzheng Li; Chaoqun Ma; Tengbo Yang; Zhifeng Wu; Rui Yao; Guosong Zhao; Xiaojv Ning; Peng Kang (Urban Climate, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Soil organic carbon trade-offs under conservation tillage: Carbon stock versus stability mediated by particulate and mineral-associated fractions - Rui Jiang; Shuai Liu; Fahui Jiang; Zichun Guo; Samuel Adingo; Zengming Chen; Lei Gao; Xinhua Peng (Soil and Tillage Research, 2025)

Remote sensing of vegetation phenology in the northern hemisphere from multi-channel passive microwave measurements of Chinese FengYun-3D satellite - Yipu Wang; Qingyang Liu; Rui Li; Jiheng Hu; Peng Zhang; Binbin Song (Remote Sensing of Environment, 2025)

Effects of a diet containing glutamine on the slaughter performance, meat quality, and skeletal muscle fiber types of feed-restricted yaks - Ziqi Yue; Shanpeng Ke; Liyuan Shi; Rui Hu; Zhisheng Wang; Quanhui Peng; Huawei Zou; Jianxin Xiao; Yahui Jiang; Fali Wu; Yiping Tang (Meat Science, 2025)

Spatial multiple variables and single variable updating via hydrologic system differential response method in real-time flood forecasting - Xiaoqin Zhang; Zhengyang Zhao; Rui Qin; Weimin Bao; Simin Qu; Peng Shi (Journal of Hydrology, 2025)

Advancing from historical precipitation reconstruction to real-time monitoring: Satellite-gauge fusion with near-real-time data gap-filling accounting for latency periods - Zhaode Yun; Yintang Wang; Pan Liu; Lingjie Li; Yong Liu; Cheng Chen; Rui Gao; Zhixin Peng (Journal of Hydrology, 2025)

Tailored SO2 capture in multivariate UiO-66(Zr) MOFs: Experimental insights and theoretical mechanisms - Zai-Dong Shao; Peng Wu; Fang Liu; Qi-Jun Zhang; Chao-Yang Guo; Rui-Sang Liu; Jiang Lu; Xiao-Meng Ren; Yu-Ming Zheng (Journal of Environmental Chemical Engineering, 2025)

Enhanced capacitive deionization performance of core-shell FeHCF@NiHCF Prussian blue analogue benefited from interface effect - Zewen Fan; Wannan Wang; Jing Ren; Rui-Peng Ren; Yong-Kang Lv (Journal of Environmental Chemical Engineering, 2025)

Construction of BiOBr/BiVO4 S-scheme heterojunction photocatalysts for efficient oxygen evolution from water splitting - Rui Li; Jingjing Peng; Fangxia Xie; Qing Xi; Jilong Qin; Houfen Li; Yawen Wang; Jianxin Liu; Xiaoli Ma; Xiuping Yue (Journal of Environmental Chemical Engineering, 2025)

Ureolysis-driven sulfidogenic precipitation and pH enhancement for robust bioremediation of zinc-laden acid mine drainage - Cong Peng; Zhenyu Zhang; Zhendong Yang; Li Zeng; Huijun Xi; Zhenghua Liu; Huaqun Yin; Delong Meng; Yonghong Liu; I.A. Ibrahim; Hongjuan Sun; Ke Zhang; et al. (Journal of Environmental Chemical Engineering, 2025)

A critical review of biochar-enhanced Feammox: Multilevel mechanisms and sustainable applications for nitrogen removal - Luomiao Ji; Xiaonong Zhang; Rui Zhao; Xurui Zhu; Bo Gao; Peng Wu (Journal of Environmental Chemical Engineering, 2025)

Location-specific climate and environmental benefits of China’s coal mining phase-down towards carbon neutrality - Hao Li; Tao Yang; Linman Li; Bin Lu; Tianzheng Zhang; Xiaolong Lu; Rui Peng; Zhaohua Wang (Global Environmental Change, 2025)

Experimental and molecular simulation study of in-situ self-growing nano-liquid crystal for smart water management in natural gas reservoirs - Rui Liu; Jipeng Shi; Qin Peng; Zezhou Chen; Mingqi Sun; Kang Liu; Wanfen Pu (Gas Science and Engineering, 2025)

Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2025)

Airway exposure to microplastics: Potential mechanisms from epithelial barrier damage to the development of allergic rhinitis - Xu Zhang; Mengyuan Liu; Zhiqiang Zhang; Xinyu Huang; Daoming Bai; Rui Yang; Maohua Wang; Peng Wang; Chunping Yang (Environmental Research, 2025)

Mechanistic insights into recovery of partial denitrification/anammox under continuous flow: Balancing nitrite supply and microbial competition - Rui Du; Cong Li; Shenbin Cao; Yongzhen Peng (Environmental Research, 2025)

Synergistic lattice engineering and surface passivation via cerium modification for robust ultrahigh-nickel layered oxide cathodes - Lunhao Deng; Rui Zhou; Jie Chen; Xiaotian Xu; Yuanyuan Chen; Xinyu Zhao; Liang Luo; Wang Xiang; Xiangwan Lai; Yingjie Zhang; Xianshu Wang; Ding Wang; et al. (Chemical Engineering Journal, 2025)

Carbon-modulated DPAOs metabolism drives high-rate denitrifying phosphorus removal with nitrate as the Electron acceptor in granular sludge systems - Rui Du; Duanyuan Xu; Xinpeng Xi; Shenbin Cao; Yongzhen Peng (Chemical Engineering Journal, 2025)

Mechanistic insights for DOM removal and membrane fouling mitigation: Optimizing Ferrate(VI)/AlCl₃ pretreatment and revealing the synergistic effect - Rui Zhang; Shaoyin Peng; Zhenbei Wang; Fei Qi; Chen Li; Yatao Liu; Fan Li; Amir Ikhlaq; Jolanta Kumirska; Ewa Maria Siedlecka; Oksana Ismailova; Zukhra Kadirova (Chemical Engineering Journal, 2025)

Enzyme-assisted structural characterization of ulvan from Ulva pertusa by hydrophilic interaction liquid chromatography coupled with mass spectrometry - Chunying Du; Xinyu Wang; Leke Qiao; Kaixuan Bu; Yinglu Wu; Rui Xiao; Peng Wang (Carbohydrate Polymers, 2025)

How topographic and pedological factors affect vegetation responses to drought: a study from the Qinling Mountains, China - Chao Li; Zhao Jin; Chengcheng Jiang; Yanjun Shen; Rui Wang; Jianbing Peng (CATENA, 2025)

High-yield synthesis of biomass-derived carbon dots for enhanced taraxacum growth - Guanxiong Liu; Hui Wang; Jiaxin Dong; Yinying He; Rui Wang; Xiangli Li; Dongyue Liu; Jing Duan; Jing Feng; Xiaoyu Lu; Lijuan Gui; Sheng Hou; et al. (Biomass and Bioenergy, 2025)

Biomass pyrolysis characterisation based on machine learning: identification of key factors affecting biochar stability - Peng Zhang; Bing Wang; Hui Liu; Yang Rui; Guomin Li; Jian Zhang (Biomass and Bioenergy, 2025)

Multiomics integration unveils rapeseed adaptative responses to potassium deprivation: a synergy of morpho-physiological, transcriptomic, and metabolic reprogramming - Rui Cui; Si-si Sun; Min-nan Pei; Ying Liu; Yu-shan Xiao; Ying-na Feng; Ting Zhou; Ying-peng Hua (Plant and Soil, 2025)

Real-time rockburst warning using microseismic multi-feature parameters based on the PSO-GRNN model - Wen Xuan Dong; Qing He Zhang; Xiao Rui Wang; He Peng Dong; Chuan Bing Wang; Sheng tao Wang (Natural Hazards, 2025)

The comprehensive review of eucalyptol: synthesis, metabolism, and therapeutic applications in disease treatment - Bin Yao; Bin He; Jiahua Peng; Xin Song; Rui Zhao; Yu Sun; Yanfang Zhang (Molecular Biology Reports, 2025)

Antibacterial and antibiofilm efficacy of TMC647055 against methicillin-resistant Staphylococcus aureus - Jiale Wu; Qing Zhu; YunXue Bai; Lei Yuan; Peng Liu; Rui Zhao (Archives of Microbiology, 2025)

Critical processes controlling the formation of visible gold in the giant Jiaodong gold province: Constraints from microtextural and geochemical analyses by SEM, TOF–SIMS, and LA-(MC)-ICP-MS - Hong Wang; Ting-Guang Lan; Lang-Ye Zhao; Hong-Rui Fan; Zhan-Ping Li; Huan-Long Hu; Zi-Qi Xu; Hong-Wei Peng; Lei Shu (Acta Geochimica, 2025)

Simulation on the propagation characteristics of TEM pseudo-wavefield - Jun-jie Xue; Ke-rui Fan; Xin Wu; Zhi-peng Qi; Wen-han Li; Jiang-wei Cui (Applied Geophysics, 2025)

A novel leaching-extraction synergistic approach for NdFeB scrap recycling: Dual-functional liquid leaching and highly selective non-aqueous phase extraction - Jinshui Mao; Juan Liu; Sili Ren; Rui Liu; Tianyi Peng; Xiaocheng Li (Process Safety and Environmental Protection, 2025)

ZmPOD5 positively regulates drought tolerance by modulating ROS production - Rui Li; Jian Li; Minghao Sun; Yang Qin; Yunling Peng; Yiru Wang; Jun Zheng (Plant Science, 2025)

Hydrodynamic characteristics of horizontal-axis tidal turbine with Gurney Flap and vortex generators - Yonghui Liu; Yuqi Liu; Yu Xue; Junzhe Tan; Peng Yuan; Xiancai Si; Zhen Pei; Rui Shu; Xiaodong Liu (Ocean Engineering, 2025)

Integrated assessment of chromium exposure risk from agricultural soils using chemical extraction, in vitro simulation, and mouse bioassay - Peng Xiao; Yi Zhou; Pengfei Wang; Rui Li; Shimao Xiong; Xiyan Jiang; Yunpeng Li; Yue Wu; Yuntao Yang; Xiaolin Cai; Naiyi Yin; Yanshan Cui (Journal of Hazardous Materials, 2025)

Biofilm-engineered nitrite transfer channeling from comammox to anammox drives autotrophic nitrogen removal in low-strength municipal wastewater - Da Jin; Rui Zhao; Xiaonong Zhang; Xingxing Zhang; Peng Wu (Journal of Environmental Management, 2025)

Long time-series planktonic ecosystem stability assessment and obstacle factor analysis in the Changjiang River estuary, China - Rui Gu; Yang Peng; Yifeng Shi; Laxman Pujari; Yuanliang Zhao; Dazhi Wang; Jun Sun (Journal of Environmental Management, 2025)

Millimeter-scale interactions of nitrogen and potassium on denitrification, anammox, and Feammox in soil fertilization zones - Jingjing Lyu; Rui Tian; Runhua Zhang; Peng Chen; Xinxin Jing; Runqin Zhang; Kang Zhao; Yi Liu; Chenhao Lyu; Zhiguo Li (Journal of Environmental Sciences, 2025)

Stationary asperity stress drop during controlled 3D tensile fracture propagation - Rui Wu; Fuqiang Gao; Shuangyong Dong; Xiangyuan Peng; Shuwen Cao; Bing Qiuyi Li (International Journal of Rock Mechanics and Mining Sciences, 2025)

Gas permeability characteristics and pore structure evolution of sandstones with high-temperature damage effects - Jiang-Feng Liu; Hong-Yang Ni; Xu Chen; Shi-Jia Ma; Zhi-Peng Wang; Rui-Nian Sun (International Journal of Rock Mechanics and Mining Sciences, 2025)

Insights into the key odorants in Chimonanthus praecox var. concolor Mak. Flower using the sensomics approach - Peng Guo; Wei Guan; Runhu Xin; Yuanhao Zhou; Miao Liang; Yajian Wu; Rui Wang; Yuping Liu (Food Chemistry, 2025)

Impact of domestic and industrial effluent discharge on the microbiome of river sediments from the middle and lower reaches of the Yangtze River - Rui Bian; Xiaofeng Cao; Jianfeng Peng; Weixiao Qi (Environmental Research, 2025)

Mass concentration, spatial distribution, and risk assessment of small microplastics (1–100 μm) and nanoplastics (<1 μm) in the surface water of Taihu Lake, China - Qingcun Li; Qingsheng Bai; Ronggang Zheng; Peng Li; Rui Liu; Sujuan Yu; Jingfu Liu (Environmental Research, 2025)

Impacts of different types of wastewater discharge on plankton community structure in the receiving rivers of the Yangtze River - Rui Bian; Shier Huang; Xiaofeng Cao; Weixiao Qi; Jianfeng Peng; Huijuan Liu; Min Chen; Yufeng Chen; Jiuhui Qu (Environmental Pollution, 2025)

Field-based analysis of CO2 direct expansion heat pump systems for sustainable heating in cold regions: A case study - Yuwei Fan; Yi-Zhou Wang; Pei Li; Xiaolong Li; Jianguo Yang; Xuyan Song; Zhao-Rui Peng; Chunhua Qi; Xin-Rong Zhang (Energy and Buildings, 2025)

Dual-stage reverse-dialysis-engineered cartilage-biomimetic hydrogels: Highly resilient anti-swelling double-layer architectures - Zheng-Feng Zhang; Mei-Yan Ling; Xiao-Rui Ge; Jia-Ying Chen; Bei Zhang; Xiao-Hui Yao; Peng Song; Wei-Guo Zhao; Dong-Yang Zhang; Jun Wang (Chemical Engineering Journal, 2025)

Air layer-engineered Cf@void@SiCnf composites for enhanced electromagnetic wave absorption - Wenzhao Geng; Limeng Song; Yilin Liu; Haoyuan Lei; Peng Liang; Linan Wang; Hailong Wang; Yanqiu Zhu; Mi Tian; Rui Zhang; Zhiyu Min; Bingbing Fan (Chemical Engineering Journal, 2025)

UV-switchable dual-mode sensing in a lead-free CsCu2I3 perovskite sensor for selective detection of mixed amines - Rui Wu; Qingyi Guan; Mingji Xu; Ruixiang Li; Shu Chen; Chunhua Luo; Hui Peng; Hechun Lin (Chemical Engineering Journal, 2025)

Mo-Nitrogen nexus: Nanotechnology enhanced Mo-based nitrogen fixation towards environmental sustainability - Samina Irshad; Yu Xie; Yaping Lyu; Ziqi Zhang; Xingxin Liu; Haojie Wei; Beza Tuga; Christy L. Haynes; Yaqi Jiang; Yi Sun; Jason C. White; Yukui Rui; et al. (Chemical Engineering Journal, 2025)

FeCl3-integrated PD/A process for municipal wastewater treatment: Enabling synergistic N and P removal under carbon-limited and short-HRT conditions - Meihui Tang; Shenbin Cao; Rui Du; Yongzhen Peng (Chemical Engineering Journal, 2025)

Modification of oceanic lithospheric mantle by percolated melts sourced from recycled ancient crust: Evidence from Ca Os isotopes of refractory harzburgites - Hui-Chao Rui; Olivier Namur; Dong-Yang Lian; Peng-Jie Cai; Jie Li; Yurisley Valdes-Mariño; Jing-Sui Yang; Hong-Ping He (Chemical Geology, 2025)

Timosaponin B- II Enhances Osteogenic Differentiation of Human Periodontal Ligament Stem Cells via PI3K/AKT/GSK3β Signaling Pathway - Dai-Wei Yang; Xiao-Bin Cui; Rui Dong; Zhao-Yan Wu; Yu-Xing Zhang; Peng Yang; Jun Zhang (Stem Cell Reviews and Reports, 2025)

Phosphorylation of a conserved TBXT threonine residue is vital to vertebral development - Shuxia Chen; Chennan Liu; Ying Zhao; Lingbo Wang; Rui Peng; Lei Lu; Qian Yu; Yichen Jin; Jinsong Li; Xueyan Yang; Yunping Lei; Hongyan Wang (Science China Life Sciences, 2025)

Multifunctional fluorescent sensors N/CDs@Eu-MOFs for rapid detection of childhood obesity and acute myeloid leukemia biomarkers and identification of chiral enantiomers of lysine - Liping Peng; Rui Xue; Henglong Ren; Borong Ren; Mingyue Wang; Xiuli Niu; Hao Guo; Wu Yang (Analytica Chimica Acta, 2025)

Protective effects of melatonin pretreatment on oxidative damage and immune system impairment in Eriocheir sinensis exposed to ammonia-N stress: insights from the intestine-hepatopancreas axis - Rui Wang; Hui Peng; Dapeng Li; Rong Tang (Aquaculture International, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Effects of probiotics, prebiotics, and synbiotics on cardiometabolic risk factors in children and adolescents with overweight or obesity: a systematic review and Bayesian network meta-analysis - Liang Zhang; Fang Wang; Rui Wang; Bowen Sun; Peng Ju Liu (Critical Reviews in Food Science and Nutrition, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Nitric oxide regulates spindle dynamics to modulate the maturation of goat oocytes - Rui Xu; Zhi Zheng; Weizhao Bai; Minghui Liu; Sihai Lu; Sha Peng; Menghao Pan; Baohua Ma (Theriogenology, 2025)

Seismic performance assessment for high CFRD on thick layered deposit considering various reinforcement measures - Zhao Wang; Wenming Peng; Jian-Min Zhang; Rui Wang (Soil Dynamics and Earthquake Engineering, 2025)

Crop diversification improves productivity and soil health by regulating fungal diversity - Rui Li; Zhibin He; Peng He; Rong Yang; Dengke Ma; Yuan Li; Yangzhou Xiang; Weihao Sun; Xi Zhu; Zhixin Zhang (Soil and Tillage Research, 2025)

Impact of calcium alginate gel-urea modified dry water on free radical spectral signatures and suppression mechanisms in methane explosions - Bin Peng; Qiuhong Wang; Jun Deng; Chi-Min Shu; Guoqiang Dong; Qingfeng Wang; Chao Ma; Rui Guo; Jianxiong Liu (Process Safety and Environmental Protection, 2025)

Opening of South China Sea in the Western Pacific forcing the climate cooling and lake level rise at Eocene–Oligocene transition - Jing Guo; Fujie Jiang; Guangrong Peng; Yuqi Wu; Weibing Shen; Rui Zhang; Yu An; Dapeng Jiang; Fusheng Yu; Yaqi Li; Zhifeng Yu; Jiabing Jiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A new genus and species of Susumaniidae (Insecta: Phasmatodea) from the Middle Jurassic of Shaanxi Province, Northwest China - Qi-Ming Guo; Chun-Peng Xu; André Nel; An-Cheng Peng; Zhi-Gang Wen; Ting Li; Rui Fang; Da-Ran Zheng (Palaeoworld, 2025)

Skeleton engineering of conjugated microporous polymer for highly efficient PM capture in harsh environments - Cailin Guo; Wei Liu; Mengxue Li; Peng Mu; Anli Yi; Zhaoqi Zhu; Rui Jiao; Hanxue Sun; An Li (Journal of Hazardous Materials, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Advances in the application of carbon materials for anammox enhancement: A comprehensive review - Bo Gao; Xiaonong Zhang; Rui Zhao; Xurui Zhu; Luomiao Ji; Peng Wu (Journal of Environmental Management, 2025)

Synergistic quorum quenching to the diffusible signal factor and AHLs mediated quorum sensing in Thiothrix controlling filamentous sludge bulking - Rui Liu; Lin Feng; Jie Li; Zhuo-Li Yan; Jian-Hong He; Yue Zhi; Xiao-Wei Xu; Peng Yan; You-Peng Chen (Journal of Environmental Chemical Engineering, 2025)

Changes and responses of GPP among different plant functional types in a savanna ecosystem under future climate scenarios - Weiduo Chen; Xuehai Fei; Jingyu Zhu; Rui Chen; Haiqiang Du; Yingqian Huang; Yong Zhang; Yi Shen; Aping Niu; Peng Xu (Journal of Environmental Management, 2025)

Influence and mechanism of polyethylene microplastics on antibiotic resistance genes and microbial community in sludge composting process - Jie Yang; Rui Jiang; Yingchun Li; Weijian Liu; Mengmeng Wang; Peng Ren (Journal of Environmental Chemical Engineering, 2025)

Surface self-assembly of tannic acid network to enhance wastewater treatment and oil-water separation performance of dual-bismuth BiOBr–BiOCOOH/PVDF membranes - Dong Chen; Rui Zhang; Jie He; Maoqin Xu; Zixi Li; Yujie Liu; Lin Peng (Journal of Environmental Chemical Engineering, 2025)

“Phenology description is all you need!” mapping unknown crop types with remote sensing time-series and LLM generated text alignment - Siyuan Wen; Wenzhi Zhao; Fengcheng Ji; Rui Peng; Liqiang Zhang; Qiao Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

The influence of pulsed electric fields with different waveforms on the extraction of valuable compounds from microalgae - Liuxia Li; Yifan Gao; Zihuang Peng; Xun Pei; Ruorong Hua; Fuchang Lin; Rui Zhang; Yi Liu (Innovative Food Science & Emerging Technologies, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Nickel complex-bridging to enhance electron transport in covalent organic frameworks for efficient photocatalytic uranium reduction - Xiao-Xing Wang; Rui Zhang; Zhi-Hai Peng; Jing-Wen Gong; En-Min Hu; Cheng-Peng Niu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Differences in the home-field effects of litter decomposition modulate changes in soil microbial nutrient limitations: insights from eco-enzyme stoichiometry - Yongxia Meng; Peng Li; Lie Xiao; Jialiang Liu; Chaoya Zhang; Shutong Yang; Xiaoming Zhang; Yunqi Wang; Tian Wang; Rui Wang (CATENA, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Iron and Ferritin Dyshomeostasis Intersect with Sex, Age, and Disease Severity in Amyotrophic Lateral Sclerosis - Xiaoge Xie; Peng Wu; Ting Wen; Rui Jia; Ronghua Zhang; Fangfang Hu; Jiaoting Jin; Xing Qin; Qiao Yi Chen (Journal of Molecular Neuroscience, 2025)

Revealing the occurrence characteristics, interaction mechanisms, and health risk of phthalates in agricultural soil of arid regions across Northwest China - Guo-dong Kang; Peng Lei; Lei-lei Lu; Ning Wang; Meng-jiao Li; Liang-liang Liu; Rui-yun Sun; Sheng-hu Zhang; Yan-hua Liu; Ping Wu (Environmental Monitoring and Assessment, 2025)

YOLO-feed: An advanced lightweight network enabling real-time, high-precision detection of feed pellets on CPU devices and its applications in quantifying individual fish feed intake - Miaosheng Feng; Pengxin Jiang; Yuhang Wang; Shuimu Hu; Sijing Chen; Rui Li; Haibin Huang; Ning Li; Boyu Zhang; Qiaozhen Ke; Yu Zhang; Peng Xu (Aquaculture, 2025)

Telaprevir attenuates caspase-11-dependent pyroptosis in mouse heart following ischemia/reperfusion via inhibition of MALT1/TRAF6 pathway - Ming-Rui Li; Bi-Feng Yao; Can Tang; Xiu-Ju Luo; Jun Peng (Toxicology and Applied Pharmacology, 2025)

Tectorigenin alleviates irinotecan-induced intestinal inflammation by activating the Nrf2/Keap1 pathway and synergistically enhances the anti-colon cancer efficacy of irinotecan - Rui Ma; Xiaoya Liu; Peng Zheng; Guijun Zou; Chaojun Zhang (Toxicology and Applied Pharmacology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Magnesium salt-synergistic roasting of mixed rare earth concentrate: killing two birds with one stone for enhanced rare earth leaching and fluorine fixation - Jiahao He; Yifan Zhang; Shuai Yuan; Rui Han; Peng Gao (Process Safety and Environmental Protection, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Decoupling erosion effects on carbon fractions and stability in black soil agricultural landscapes - Rui QIAN; Lei GAO; Asim BISWAS; Hao DU; Shuai LIU; Xinhua PENG (Pedosphere, 2025)

Cyclic organic matter accumulation in a plateau salinized lacustrine basin: Major controls and hydrocarbon significance - Peng Pang; Di Xiao; Kunyu Wu; Songtao Wu; Haoting Xing; Ying Xiong; Rui Liu; Xiucheng Tan (Marine and Petroleum Geology, 2025)

Coupling mechanisms and zonation characteristics of sulfur and iron in clayey aquitards under the influence of lake and groundwater - Ziqi Peng; Teng Ma; Rui Liu; Wenkai Qiu; Kun Lei; Juan Chen (Journal of Hydrology, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

Mechanistic insights into electric field-driven specific ion effects on nanoplastics aggregation in heavy metal co-contaminated aquatic systems - Yan Peng; Rui Li; Ying Tang; Xinmin Liu; Yaowu Zhang; Xinping Gao; Kai Wang; Rui Tian; Hang Li (Journal of Hazardous Materials, 2025)

Genome-wide association and epidemiological evidence linking air pollution to aging mechanisms - Xiao-Yu Liu; Dong Peng; Xu-Rui Liu; Yuan-Hui Sheng; Jun-Nan Zhao; Rong-Bin Xu; Dan Zhang; Bo Chen (Journal of Hazardous Materials, 2025)

Rhizobial symbiosis modulates mercury accumulation and metabolic adaptation under hydrological extremes - Rui Liu; Kevin D. Oliphant; Zhuyuan Xia; Zhe Chen; Ruimin Hou; Ruijie Zhang; Tong Peng; Robert Hänsch; Dingyong Wang; Heinz Rennenberg; Bin Hu (Journal of Hazardous Materials, 2025)

Ionic liquid modified MOF-808 for efficient adsorption and stable capture of radioactive iodine - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Wen-Rui Zhang; Xiang-Hua Qi; Chun-Hui Gong; Peng Wang; Man-Li He; Yi Yang (Journal of Environmental Management, 2025)

Deep-sea rare earth element-rich sediments: A review of distribution, carriers and petrogenesis - Yu Fu; Zhengkun Li; David Chew; Pete Hollings; Jinzhou Peng; Jieyun Chen; Bojue Tan; Gaowen He; Yongjia Liang; Fei Huang; Yayue Tang; Rui Wang; et al. (Global and Planetary Change, 2025)

Computer-aided precise hapten design strategy for the monospecific detection of altrenogest: Experimental validation and analysis of the molecular recognition mechanism - Hongfei Yang; Hao Wen; Yu Si; Mingyue Ding; Yiting Liu; Ziyan Yu; Linwei Zhang; Jiacan Wang; Xiaoming Pan; Shiyun Han; Yiting Wang; Shixiang Wu; et al. (Food Chemistry, 2025)

Integration of human sensory evaluation, intelligent E-tongue/E-nose systems, microbiomics, and metabolomics to comprehensively analyze flavor characteristics and dietary improvement mechanisms of processed Buddha's hand fruit - Zi-Xuan Ding; Yue-Hua Chen; Jia-Nuo Zhang; Wen-Yu Wang; Xin-Ru Zhang; Rui-Bo Sun; Hui Zhang; Ming Xie; Hui-Peng Song (Food Bioscience, 2025)

Tailoring reactivity in MOF derivatives via thermally induced amorphization: Synergistic crystalline/amorphous heterointerfaces for efficient 4-nitrophenol detoxification - Wenyao Zhang; Mian Wang; Rui Xiong; Kai Wei; Genping Zhu; Wei Ye; Wei Wang; Haijiao Xie; Peng Gao; Gan Jia (Chemical Engineering Journal, 2025)

Carrier-free methylene blue nanomedicine for prolonged hepatic visualization in anatomical hepatectomy: A translational study from bench to bedside - Hu Chen; Minglei Teng; Qihui Hu; Xiaoliu Liang; Hui Liu; Zhenjie Li; Xing Gao; Yisheng Peng; Xiaoyong Wang; Syed Faheem Askari Rizvi; Yi Lv; Hongwei Cheng; et al. (Chemical Engineering Journal, 2025)

Nitrogen-removal improvement and the mechanisms using a composite carbon source synthesized by alkali-modified cherrywood and polyhydroxybutyrate-co-valerate in an aerated solid-phase biofilter treating saline and low C/N ratio wastewater - Guixi Yao; Xiaoqian Cheng; Qing Li; Peng Zhou; Peiwu Liu; Rui Han; Yinghai Wu (Chemical Engineering Journal, 2025)

An integrated biorefinery strategy for fractionating high-molecular-weight hemicellulose and uncondensed lignin based on tetrapropylammonium hydroxide system - Rui Tian; Bolang Zhu; Jing Li; Xinyuan Zhang; Baozhong Lü; Jing Bian; Jialong Wen; Zhengjun Shi; Yuetong Kang; Feng Peng (Chemical Engineering Journal, 2025)

Monolayer graphene interlayer enhanced flexible gas sensor with fast response and high strain tolerance for wearable ammonia monitoring - Chen Wang; Ziran Wang; Feng Xu; Luyang Zhang; Haoyu Yuan; Zaiyu Zhang; Chaqi Gai; Zhongjing Ren; Haipeng Wang; Rui You; Peng Yan (Chemical Engineering Journal, 2025)

Correction to: Effect of Dissolved Oxygen on Poly (3‑Hydroxybutyrate‑co‑3‑Hydroxyvalerate) Solid‑Phase Denitrification: Simultaneous Nitrification and Denitrification Performance and Microbial Community - Peng Zhou; Ying Liu; Xin Su; Peiwu Liu; Rui Han (Water, Air, & Soil Pollution, 2025)

Root-soil-microbe interactions mediate phosphorus and iron uptake from lithium iron phosphate nanomaterials - Yaqi Jiang; Yi Sun; Changcheng An; Pingfan Zhou; Yuanbo Li; Quanlong Wang; Jason C. White; Yukui Rui; Peng Zhang (Applied Soil Ecology, 2025)

MOF-on-MOF nanomaterial (Fe-MOF@UiO-66)-based ratiometric fluorescence/colorimetric dual-mode sensor for ultrasensitive detection of uric acid - Tao Lian; Rui Peng; Zhengyue Xiao; Xiaomin Tang; Peng Xu; Yu Hu; Ping Qiu (Analytica Chimica Acta, 2025)

Microplastics Induce Structural Color Deterioration in Fish Poecilia reticulata Mediated by Oxidative Stress - Hong-Yu Ren; Huan-Chao Ma; Rui-Peng He; Cong-Cong Gao; Bin Wen; Jian-Zhong Gao; Zai-Zhong Chen (Fishes, 2025)
Microplastics (MPs) can affect fish health by inducing oxidative stress, but their impact on structural coloration remains poorly understood. This study investigated the effects of environmentally relevant concentrations (16 and 160 μg/L) of MPs and nanoplastics (NPs) exposure on growth, oxidative stress and structural coloration in blue strain guppy fish (Poecilia reticulata). Results showed exposure to 160 μg/L MPs significantly reduced specific growth rate of fish compared to controls. Plastic accumulation followed a dose-dependent pattern, especially within gut concentrations. Oxidative stress responses differed between MPs and NPs: 160 μg/L MPs decreased SOD activity in skin and reduced GSH levels, while 160 μg/L NPs increased MDA levels in gut tissues, indicating severe lipid peroxidation. Structural coloration analysis revealed exposure to 160 μg/L MPs decreased lightness and increased yellowness, demonstrating reduced blue coloration. This was accompanied by an increase in skin uric acid content, suggesting that guanine conversion might occur to combat oxidative stress. These findings demonstrate that MPs, particularly at high concentrations, impair growth and induce oxidative stress in guppies. To counteract stress, guanine in iridophores may be converted into uric acid, leading to a decline in structural coloration. This study is the first to reveal that MPs disrupt structural coloration of fish, providing new insights into the ecological risks of plastic pollution on aquatic organisms.

Multi-target directed ligands design of 1-O-Acetylbritannilactone derivatives: Dual anti-neuroinflammatory and acetylcholinesterase inhibitory activities - Yan-Peng Liang; Qian Gao; Hong Chen; Rui Ma; Xiao-Bo Zhao; Xiao-Jie Jin; Jian Zhang; Yan-Ping Shi; Wei Ha (Phytochemistry Letters, 2025)

Flavonoids and butanolides from the bark of Machilus robusta and their bioactivities - Rui-Qi Liu; Shan-Shan Ling; Xian-Da Hu; Bing Peng; Yan-Ru Li (Phytochemistry Letters, 2025)

Mitigation of arsenic uptake and accumulation in rice grains by applying husk-derived silicon in a synergistic way: Evidence from pot and field trials - Xianghong LI; Xin WANG; Xionghui JI; Jingmin YANG; Yunping YU; Rui HUANG; Bo PENG; Baoshan XING (Pedosphere, 2025)

Optimization of discharge parameters for high-voltage pulse crushing technology − A review - Bo Zhang; Rui Han; Peng Gao; Shuai Yuan; Yanjun Li; Honghao Zhang (Minerals Engineering, 2025)

Insights into ROL-driven and ROS-mediated metalloid oxidation and sequestration in the soil-rice iron barrier system - Jing-Min Yang; Xin Wang; Dong-Xing Guan; Rui Huang; Xiong-Hui Ji; Yun-He Xie; Bo Peng; Qin-Bo Qin (Journal of Hazardous Materials, 2025)

Assessing the nicotinic acetylcholine receptor-mediated enantioselective neurotoxicity of a neonicotinoid-like pollutant, chiral sulfoxaflor: Insight from the two asymmetric centers - Zhi-Cong He; Tao Zhang; Xin-Fang Lu; Rui Li; Wei Peng; Qiong Mei; Qi-Zhao Wang; Fei Ding (Journal of Hazardous Materials, 2025)

Improvement of nutritional value of cotton residue by solid state fermentation - Duoting Wu; Xiurong Liang; Rui Hu; Zhisheng Wang; Huawei Zou; Fali Wu; Hui Li; Yahui Jiang; Quanhui Peng; Jianxin Xiao; Hongbo Li; Zhenyong Zhou (Journal of Environmental Chemical Engineering, 2025)

Light-driven nitrogen fixation catalyzed by nanomaterials: link between PNF and BNF - Jiahui Feng; Yi Sun; Yukui Rui; Peng Zhang; Jason C. White; Yuheng Zhang (Environmental Research, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Multifunctional Janus hydrogel targeting mitochondrial regulation and inflammatory pathways promotes infected burn wound repair - Xiaohui Li; Longbao Feng; Honglin Wu; Hao Yang; Peng Wang; Yongfei Chen; Yuxi Zhou; Jiayuan Zhu; Wei Xue; Rui Guo; Zhicheng Hu (Chemical Engineering Journal, 2025)

Polycomponent metal-organic frameworks of substituent polydispersion hydroxypropyl-β-cyclodextrin as inhalable drug carrier - Xiaojian He; Huipeng Xu; Xiangyu Zhao; Feng Li; Ningning Peng; Jialong Wang; Wenqiang Hua; Feixiang Wang; Guanghong Xu; Rui Yang; Jiwen Zhang; Li Wu (Carbohydrate Polymers, 2025)

Coupled mutual feedback and interaction mechanisms among the geological environment, ecological environment and human activities in the Qinling Mountains - Chao Li; Zhao Jin; Chengcheng Jiang; Yanjun Shen; Rui Wang; Jianbing Peng (Science China Earth Sciences, 2025)

Females adapted better than males in Populus deltoides to simulated nitrogen deposition - Fang He; Shu-Ying Wei; Rui-Quan Wang; Jia Yao Tang; Peng Yang; Ting Wang; Jin-Liang Huang; Gang Chen; Tian-Tian Lin (Plant and Soil, 2025)

Regional Wave Spectra Prediction Method Based on Deep Learning - Yuning Liu; Rui Li; Wei Hu; Peng Ren; Chao Xu (Journal of Marine Science and Engineering, 2025)
The wave spectrum, as a key statistical feature describing wave energy distribution, is crucial for understanding wave propagation mechanisms and supporting ocean engineering applications. This study, based on ERA5 reanalysis spectrum data, proposes a model combining CNN and xLSTM for rapid gridded wave spectrum prediction over the Bohai and Yellow Seas domain. It uses 2D gridded spectrum data rather than a spectrum at specific points as input and analyzes the impact of various input factors at different time lags on wave development. The results show that incorporating water depth and mean sea level pressure significantly reduces errors. The model performs well across seasons with the seasonal spatial average root mean square error (SARMSE) of spectral energy remaining below 0.040 m2·s and RMSEs for significant wave height (SWH) and mean wave period (MWP) of 0.138 m and 1.331 s, respectively. At individual points, the spectral density bias is near zero, correlation coefficients range from 0.95 to 0.98, and the peak frequency RMSE is between 0.03 and 0.04 Hz. During a typical cold wave event, the model accurately reproduces the energy evolution and peak frequency shift. Buoy observations confirm that the model effectively tracks significant wave height trends under varying conditions. Moreover, applying a frequency-weighted loss function enhances the model’s ability to capture high-frequency spectral components, further improving prediction accuracy. Overall, the proposed method shows strong performance in spectrum prediction and provides a valuable approach for regional wave spectrum modeling.

Two new acorane-type sesquiterpenoids from an endophytic Trichoderma harzianum associated with Paeonia lactiflora Pall - Yun-Peng Sun; Man-Li Zhang; Yang Yu; Ran Sun; Si-Rui Wang; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Streptococcus suis AdcA interacts with factor H and inhibits C3b deposition on the bacteria to participate in complement evasion - Siqi Pang; Zhulin Qiao; Jiajia Xu; Hao Tang; Qiuhong Zhang; Weiyao Han; Lu Peng; Jiaojiao Yang; Jiao Zhang; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2025)

An oral recombinant human type 5 adenovirus vector vaccine encoding the S protein of Type I feline coronavirus effectively protection against FCoV challenge in cats - Gu-nan Deng; Chang-zhan Xie; Ke-lei Zhou; Chun-sai He; Yuan-Zhen Ma; A.-jia Ake; Rui Guo; Kai Li; Chen Peng; Bin Zhang (Veterinary Microbiology, 2025)

Sesquiterpenoids isolated from the root bark of Lycium chinense - Xiao-xia Wang; Qian Liu; Ning Wang; Rui-li Zhang; Xiao Li; Peng-yu Zhuang; Hang Liu; Liang-dan Sun; Yang Jin (Phytochemistry, 2025)

Investigation of aerodynamic performance and operational optimization of wing sails at varying spacings - Rui Zhang; Lianzhong Huang; Guisheng Peng; Zhang Ruan; Ranqi Ma; Kai Wang; Jianlin Cao; Jianyi Wu; Xiaowu Li (Ocean Engineering, 2025)

Propagation threshold from meteorological to agricultural drought and its potential influence factors - Peng Sun; Ruilin Liu; Rui Yao; Xihui Gu; Aminjon Gulakhmadov; Dongdong Kong; Xiang Zhang (Journal of Hydrology, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Multidimensional analysis of sensory perception and neurophysiological responses to marinated beef cooked by diverse methods - Tianyi Yang; Wei Jiang; Chencheng Luo; Jin Hu; Wei Xu; Peng Zhang; Xiaofei Jin; Yuxuan Zhou; Rui Liu; Zhiyu Qian; Yamin Yang (Innovative Food Science & Emerging Technologies, 2025)

Substrate type-driven differences in interfacial microbial community and pathogenic risk: Clay, microplastics and activated carbon - Taishuo Zhang; Wenfu Wang; Xiang Zhi; Xiaoqian Ye; Rui Wang; Jiarui Zhao; Jiamin Dai; Hong Qiang; Peng Liu; Hanzhong Jia (Gondwana Research, 2025)

Emerging MXene-based catalysts for advanced oxidation processes - Yanlei Zhu; Ning Li; Rui Wang; Longfei Zhang; Yong Liu; Wenchao Peng; Jiapeng Liu (Fuel, 2025)

Effects of organic acids on the physico-chemical and functional characteristics of mung bean globulin amyloid fibrils - Peng Jiang; Shu Zhang; Tianxin Fu; Jingru Sun; Rui Ma; Xuejian Song; Jingjing Diao; Zhijiang Li; Changyuan Wang (Food Bioscience, 2025)

Z-scheme CoS/Bi4O5I2 heterostructure for visible light catalytic degradation of tetracycline hydrochloride: Degradation mechanism, toxicity evaluation, and potential applications - Dongyuan Li; Xiaojun Peng; Rui Zhang; Yadong Chen; Xianwei Dai; Wenling Wang (Environmental Research, 2025)

An innovative and efficient approach for slope reliability analysis: Machine learning based surrogate modeling with advanced attention mechanisms - Nenghao Huang; Yu Han; Weiwei Xie; Rui Hu; Hao Peng; Guanxian Song; Menglan Wu; Menglong Zhu; Hua Wei; Ming Liang (Engineering Geology, 2025)

Rising disparities in grain self-sufficiency across China: Provincial divergence amidst overall national improvement - Xiaoyu Yu; Rui Xiao; Zhonghao Zhang; Feng Zhou; Fei Mo; Zhenci Xu; Feng Tian; Zhi Gao; Yansheng Li; Peng Zhu; Kailiang Yu; Lumeng Liu; et al. (Environmental Impact Assessment Review, 2025)

A novel bioreactor developed for the intensification of high-viscosity aerobic fermentation processes - Qian Chen; Kai Hu; Quanfei Li; Kai Yang; Chao Zhang; Weiwei Huang; Yibin Qiu; Yian Gu; Liang Sun; Peng Lei; Jian Xue; Sha Li; et al. (Chemical Engineering Journal, 2025)

Contrasting Effects of Warming and Nitrogen Addition on soil CO2 Emission in a Semi-Arid Grassland on the Loess Plateau of China - Mingfeng Jiang; Zhun Tian; Rui Wang; Zihan Sun; Yang Peng; Chao Fang (Water, Air, & Soil Pollution, 2025)

Oil Film Detection for Marine Radar Image Using SBR Feature and Adaptive Threshold - Yulong Yang; Jin Yan; Jin Xu; Xinqi Zhong; Yumiao Huang; Jianxun Rui; Min Cheng; Yuanyuan Huang; Yimeng Wang; Tao Liang; Zisen Lin; Peng Liu (Journal of Marine Science and Engineering, 2025)
Marine oil spills pose a serious and persistent threat to marine ecosystems, coastal resources, and global environmental health. These incidents not only disrupt ecological balance by damaging marine flora and fauna but also lead to long-term economic consequences for fisheries, tourism, and maritime industries. Owing to their rapid spread and often unpredictable occurrence, timely and accurate detection is essential for effective containment and mitigation. An efficient detection system can significantly enhance the responsiveness of emergency teams, enabling targeted interventions that minimize ecological damage and economic loss. This paper proposes a marine radar-based oil spill detection method that combines the Significance-to-Boundary Ratio (SBR) feature with an improved Sauvola adaptive thresholding algorithm. The raw radar data was firstly preprocessed through mean and median filtering, grayscale correction, and contrast enhancement. SBR features were then employed to extract coarse oil spill regions, which were further refined using an improved Sauvola thresholding algorithm followed by a denoising step to obtain fine-grained segmentation. Comparative experiments using different threshold values demonstrate that the proposed method achieves superior segmentation performance by better preserving oil spill boundaries and reducing background noise. Overall, the approach provides a robust and efficient solution for marine oil spill detection and monitoring.

Assessing CO2 storage mechanisms in marine shallow sediments to mitigate leakage risks from sub-seabed carbon storage: a numerical simulation study - Gang Hu; Xiangyi Yi; Xuanhua Tian; Rui Wang; Pengchun Li; Linxiong Peng; Xi Liang (Frontiers in Marine Science, 2025)
The geological storage of CO 2 in offshore saline aquifers has been implemented at various sites worldwide. While subsea sediments can serve as a critical barrier against potential leakage from deep storage formations, the mechanisms and storage capacity for CO 2 trapping within these sediments remain inadequately understood. This study developed a two-dimensional conceptual model of shallow sediments based on the Enping15–1 Carbon Capture and Storage (CCS) project site in the South China Sea. Furthermore, the CO 2 -water-rock reaction and storage mechanism were simulated using CMG-GEM, and the process of CO 2 leakage into the sediments was investigated. The results indicate that CO 2 leakage into the shallow seabed sediments is primarily sequestered through dissolution in pore water, accounting for 70% of the total sequestration, while residual and mineral trapping contribute 10–20%. The dissolution of CO 2 leads to pore water acidification, which triggers the dissolution of anorthite and K-feldspar under the prevailing initial geochemical conditions. Dynamic reaction behavior is mainly observed at the leading edge of the acidified plume. However, if the leakage rate exceeds a critical threshold, the advancing acidified plume front causes partial dissolution of previously precipitated carbonate minerals. The critical leakage rate is determined to be 0.2 m³/day for single-point leakage and 0.3 m³/day for multi-point leakage. Notably, multi-point, low-velocity leakage enhances secondary storage within the sediment, thereby reducing the risk of CO 2 release into the overlying seawater.

Calcium phytate cross-linked polysaccharide hydrogels for selective removal of U(VI) from tailings wastewater - Lan Lei; Rui Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Xin Liu; Tie-Ying Shi; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Water Research, 2025)

Mangiferin promotes porcine oocyte maturation and delays the postovulatory aging process by up-regulating NRF2 levels - Xiuwen Yuan; Hewei Ji; Yuhao Zhang; Huilin Peng; Neng-hao Cao; Jia-jun Ren; Xue-rui Yao; Xingwei Liang; Nam-hyung Kim; Yong-nan Xu; Ying-hua Li (Theriogenology, 2025)

A novel model for predicting the ultimate bending moment of subsea pipelines with corrosion-dent coupled defects - Fuheng Hou; Yanfei Chen; Lusheng Jia; Zengli Peng; Yu Liu; Ruihao Liu; Rongfeng Zhong; Rui Li (Ocean Engineering, 2025)

Transitional chromitites within the Maqsad crust-mantle transition zone of the Semail ophiolite formed above the nascent forearc setting - Rong-Zhong Bo; Peng-Jie Cai; Dong-Yang Lian; Jing-Sui Yang; Sobhi Nasir; Hui-Chao Rui; Yu-Xiao Lu; Chu-Qi Cao; Ahmed E. Masoud (Lithos, 2025)

Zircon and apatite constraints on the key factors controlling porphyry Mo mineralization in the Shijiawan deposit: Implication for Mo metallogeny in the Qinling Orogenic Belt - Long-Long Chen; Li Tang; Peng-Rui Lv; Ya-Peng Chen; Tao Zeng (Lithos, 2025)

Efficient identification of antibiotic components in three-dimensional excitation-emission matrix fluorescence spectra via deep learning - Xu Kou; Rui Qiu; Peng Chen; Qinru Wang; Yang Chen; Hongguang Guo (Journal of Water Process Engineering, 2025)

Enhancing photocatalytic degradation of tylosin with persulfate by facile synthesis of Fe-Mo@Mo photocatalyst - Chao Gai; Xiaodi Xie; Yuecheng Jian; Yijing Tao; Rui Jin; Nana Peng (Journal of Environmental Chemical Engineering, 2025)

Experimental and consolidation modeling of flowing mud during vacuum preloading considering transient clogging and vacuum pressure attenuation - Yuefu Zhou; Rui Chen; Yuanqiang Cai; Jun Wang; Peng Wang; Dong Su; Xiangsheng Chen (Geotextiles and Geomembranes, 2025)

Discovery of novel DPP4 inhibitory peptides from egg yolk by machine learning and molecular docking: In vitro and in vivo validation - Yujie Xu; Yiqiao Pei; Zhifu Liu; Peng Tan; Rui Liu; Lulu Chu; Ye Zhang; Wenjie Wang; Hao Wang (Food Chemistry, 2025)

Corrigendum to “N-doped carbon dots/g-C3N4 photoexcitation simultaneously enhanced the microbial degradation of nitrate and oxytetracycline in a low C/N ratio aquaculture wastewater” [Chem. Eng. J. 491 (2024) 151763] - Pin Peng; Lixiang Chen; Xinyu Yan; Rui Bai; Bob Adyari; Xudong Zhou; Feng Zhao (Chemical Engineering Journal, 2025)

Development of cascade nanoreactors by fusing bone-targeting engineered extracellular vesicles to modulate bone microenvironment for treatment of diabetic osteoporosis - He Yi; Fang Depeng; Chen Xiang; Shen Hongdou; Shao Xiaoyan; Lin Jiaquan; Liu Na; Shen Tao; Wang Chengzhi; Zhang Pan; Peng Rui; Mu Jinglan; et al. (Chemical Engineering Journal, 2025)

Versatile Dual-Emissive Boron-Nitrogen Co-Doped carbon Dots: Unlocking efficient electroluminescent Light-Emitting diodes with breakthrough EQE Approaching 7% - Ming-Zhu Li; Hong-Ji Tan; Qi-Rui Liang; Jie-Rong Yu; Peng Huang; Xiao-Qi Lai; Chun-Fa Wen; Chun-Sing Lee; Qing-Xiao Tong; Jing-Xin Jian (Chemical Engineering Journal, 2025)

Highly selective and reversible adsorption of trace gaseous ammonia by a stable nanoporous carboxylic acid-functionalized silica aerogel - Zai-Dong Shao; Ting-Ting Hu; J. Paul Chen; Qi-Jun Zhang; Peng Wu; Rui-Sang Liu; Jiang Lu; Xiao-Meng Ren; Yu-Ming Zheng (Chemical Engineering Journal, 2025)

Injectable dual-network hydrogel for phototherapy and immunomodulation in the treatment of MRSA-infected and diabetic wound - Shengfei Bao; Aodi Jiang; Li Peng; Fuying Liao; Ga Liu; Li Chen; Peng Zhou; Zhen Zhu; Rui L. Reis; Subhas C. Kundu; Lian Duan; Bo Xiao; et al. (Chemical Engineering Journal, 2025)

Alkaloids of the roots of Lindera glauca (Lauraceae) and their chemophenetics significance - Zhen Peng; Jin-Yu Li; Rui Zhan; Hui-Mei Pu (Biochemical Systematics and Ecology, 2025)

Rising temperature increases the response time of LAI and GPP to meteorological drought in China - Yufei Wang; Peng Sun; Rui Yao; Chenhao Ge (Atmospheric Research, 2025)

Myricetin Mitigated Sevoflurane-induced Cognitive Dysfunction in Aged-mice Through Inhibiting Histone Deacetylase 2/nuclear Factor Erythroid 2-related Factor 2/heme Oxygenase-1 Signalling–mediated Ferroptosis and Mitochondrial Dysfunction - Peng Li; Jingjing Liu; Rui Wang; Fuyang Cao; Jiannan Li; Henglin Wang (Molecular Neurobiology, 2025)

Design, synthesis, and antifungal activity of novel pyrazole carboxamide derivatives containing benzimidazole moiety as potential SDH inhibitors - Fei Jin; Feng Peng; Xiang-Yi Kong; Wen-Rui Li; Jian-Qi Chai; Min Chen; Ai-Min Lu; Chun-Long Yang; Guo-Hua Li (Molecular Diversity, 2025)

A promising mutant strain of Pyropia haitanensis ZD-2 for floating cultivation with enhanced growth, holdfast strength, and desiccation tolerance - Yujie Wang; Qijun Luo; Juanjuan Chen; Rui Yang; Peng Zhang; Tiegan Wang; Haimin Chen (Journal of Applied Phycology, 2025)

Microfracture Mechanism and Fractal Characteristics of Sandstone with Various Prefabricated Cracks - Jiang Liu; Rui Peng; Chunyang Shen; Xuehong Yang (Geotechnical and Geological Engineering, 2025)

Global trends in staphylococcus aureus-related lower respiratory infections from 1990 to 2021: findings from the 2021 global burden of disease report - Hong Chen; Shuang Song; Rui Cui; Yong-Wang Feng; Peng Ge (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Effect of oligosaccharides from Enteromorpha clathrata on tolerance of wheat (Triticum aestivum L.) seedings to saline-alkali stress - Yinglu Wu; Chunying Du; Rui Xiao; Bo Zhu; Xiuchao Song; Xinyu Wang; Yimin Qin; Peng Wang (Algal Research, 2025)

Sedimentary and diagenetic constraints on the quality of Lower Cretaceous pre-salt lacustrine carbonate reservoirs in the Santos Basin, eastern Brazil - Junfeng Hu; Dengfa He; Rui Zhou; Huimin Ye; Tao Hu; Peng Zhang; Yongjie Hu; Baonian Wu; Shaowei Wang; Yunlei Yue (Acta Oceanologica Sinica, 2025)

Flood complexity and rising exposure risk in High Mountain Asia under climate change - Yuanyuan Bai; Dongfeng Li; Sonam Wangchuk; Albert Kettner; Yi Zhao; Rui Deng; Yong Liu; Cunde Xiao; Jinren Ni; Peng Cui (Science Bulletin, 2025)

Multi-omics analysis reveals the role of L-Glutamate in regulating cold tolerance of postharvest prune fruit - Yuanyuan Hou; Wanyu Yan; Rui Deng; Jiayi Wang; Yu Wang; Liang Wang; Jun Xing; Peng Jin; Yating Zhao (Postharvest Biology and Technology, 2025)

Mn-oxidizing microalgae and woodchip-denitrifying bioreactor system for recovering manganese and removing nitrogen from electrolytic manganese metal industrial tailwater - Xinyue Gong; Qin Peng; Ruixin Jiang; Na Yang; Cijun Xing; Rui Wang (Journal of Hazardous Materials, 2025)

Different effects of bio/non-degradable microplastics on sewage sludge compost performance: Focusing on antibiotic resistance genes, virulence factors and key metabolic functions - Xiangyu Liu; Huiyue Li; Jie Yang; Shen Yan; Yufei Zhou; Rui Jiang; Renhe Li; Mengmeng Wang; Peng Ren (Journal of Hazardous Materials, 2025)

Study on the improvement of Rye bread quality by bacterial Laccase derived from Streptomyces coelicolor - Ran Zhang; Yanhua Li; Yuan Gao; Fengyun Wang; Peng Zhou; Yan Zhang; Ying Li; Kaiyue Wang; Ting Rui; Guilan Zhu; Jingjing Wang; Zemin Fang (Journal of Cereal Science, 2025)

Extracellular polymeric substances enhanced photosynthesis over respiration in Microcystis aeruginosa - Kaikai Deng; Rui Yang; Shirong Zhang; Fang Fang; Yuanchen Huo; Peng Yan; Youpeng Chen; Jinsong Guo (Harmful Algae, 2025)

Impact of the drying process on the flavor characteristics of two economically important laver species, Pyropia haitanensis and Neopyropia yezoensis - Yuting Zhang; Juanjuan Chen; Yongbo Huang; Qijun Luo; Rui Yang; Peng Zhang; Tiegan Wang; Haimin Chen (Food Chemistry, 2025)

Antioxidant and immunomodulator nanoengineered probiotics for synergistic therapy of inflammatory bowel disease - Pandi Peng; Rui Ding; Junru Wang; Luofeng Yu; Yuxin Guo; Pengyu Chen; Tao Feng; Peng Li (Chemical Engineering Journal, 2025)

Superior matching between electrochemical and non-electrochemical reactions to boost furfural electro-oxidation - Jianyuan Deng; Rui Li; Kun Xiang; Longzhou Zhang; Kaihang Sun; Young Dok Kim; Zhongyi Liu; Jingmin Ge; Zhikun Peng (Chemical Engineering Journal, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Root exudates drive root avoidance of maize in response to neighboring wheat - Xiao-Tong Yin; Fang-Fang Zhang; Rui-Peng Yu; Na Liu; Wei-Ping Zhang; Dario Fornara; Liesje Mommer; Xue-Xian Li; Long Li (Plant and Soil, 2025)

Amplifying population exposure of extreme precipitation across Yellow River Basin, China at 1.5° C, 2.0° C and 3.0° C global warming - Rui Yao; Zice Ma; Peng Sun; Chenhao Ge (Natural Hazards, 2025)

Urbanization has enhanced compound heatwaves - Peng Sun; Shifang Yu; Rui Yao; Zhongbao Sun; Vijay P. Singh; Yaojin Bian; Chenhao Ge; Qiang Zhang (Journal of Geographical Sciences, 2025)

Simulating oasis-desert interactions in artificial and natural oasis-desert areas: Integration of remote sensing data and CFD methodology - Zhixing Peng; Shaomin Liu; Rui Liu; Xinlei He; Jin Ma; Ziwei Xu; Ji Zhou; Dongxing Wu (Agricultural and Forest Meteorology, 2025)

LncRNA OLMALINC promotes osteosarcoma progression through USP1-mediated autophagy suppression - Jianping Li; Bo Yu; Zhaowen Xue; Yiping Liang; Shanchuang Chen; Tao Gui; Zitao Liu; Lei Zhang; Rui Peng (Human Cell, 2025)

The Effect of the Marine Environment on the Distribution of Sthenoteuthis oualaniensis in the East Equatorial Indian Ocean - Shigang Liu; Liyan Zhang; Peng Lian; Jianhua Kang; Puqing Song; Xing Miao; Longshan Lin; Rui Wang; Yuan Li (Fishes, 2025)
Sthenoteuthis oualaniensis is one of the most commercially important marine cephalopod species distributed throughout tropical and subtropical waters of the Indo-Pacific Seas. The Indian Ocean is a main fishing ground for S. oualaniensis with a high population density. To explore the distribution of S. oualaniensis in the east equatorial Indian Ocean, four surveys were carried out using light-lift-net fishing vessels. Meanwhile, marine environmental data were also collected, including the sea surface temperature, sea temperature at 100 m depth, mixed layer depth, sea surface chlorophyll-a concentration, sea surface height, and eddy kinetic energy. Generalized Additive Models were used to analyze the relationship between the catch per unit effort (CPUE) for S. oualaniensis and environmental factors. The results showed that the average CPUE of S. oualaniensis was 14.55 kg/h in the four surveys, which was considerably lower than in the South China Sea and Northwest Indian Ocean. In terms of seasonal distribution, the high-CPUE stations were closer to the continental shelf in spring, while they shifted towards the deeper and offshore water in autumn, demonstrating a seasonal migration trend. Pearson correlation analysis showed that CPUE reflected a significant negative correlation with both sea temperature at 100 m depth and eddy kinetic energy (p

Neural correlates of affective forecasting in individuals with high trait anxiety: evidence from resting-state functional connectivity - An Xie; Peng Liu; Qin Zhou; Tao Chen; Dao-qun Ding; Rui-ting Zhang (Brain Imaging and Behavior, 2025)

Millennial-scale surface hydrological variability in the tropical eastern Indian Ocean linked to Northern Hemisphere high latitudes - Rui Cui; Peng Zhang; Jian Xu; Ann Holbourn; Wolfgang Kuhnt (Frontiers in Marine Science, 2025)
Surface hydrology in the tropical eastern Indian Ocean significantly impacts low-latitude climate processes including the Indonesian-Australian Monsoon and the Indian Ocean Dipole. Deciphering the evolution of surface hydrology and driving mechanisms is thus important to better understand low-latitude and global climate change. Here, we present ~206 yr-resolved temperature and salinity records of surface waters spanning the past ~31 kyr, based on δ 18 O and Mg/Ca ratio of Globigerinoides ruber from Core SO18567 retrieved offshore northwestern Australia in the tropical eastern Indian Ocean. By integrating new records with published paleo-oceanographic and -climatological records, we found that increasing sea surface temperature and decreasing salinity in the tropical eastern Indian Ocean during the Heinrich stadial 1 and the Younger Dryas could be attributed to collapse of the Atlantic Meridional Overturning Circulation (AMOC). Melting of Northern Hemisphere ice sheets would have led to a southward shift of the Intertropical Convergence Zone (ITCZ) and reduced transport of warm surface waters from the low latitudes to the Northern Hemisphere high latitudes. In addition, our results indicate that the onset of the last deglacial warming in low latitudes was linked to weakening of the Hadley circulation and AMOC due to warming of Northern Hemisphere high latitudes, rather than raised global atmospheric CO 2 concentration.

Two new phenolic glycosides from Cyathula officinalis and their relaxant effects on uterine smooth muscle - Mei-Ji Sun; Rui Zhao; Min Wen; Chun-Wang Meng; Hai-Guo Su; Fu-Xin Mi; Cheng Peng; Juan Liu; Liang Xiong (Phytochemistry Letters, 2025)

Selective anti-proliferative lignans towards TNBC cells from Knema elegans (Myristicaceae) - Zhen Peng; Xin Han; Zhao Lu; Nan Fu; Rui Zhan (Phytochemistry Letters, 2025)

Filamentous bacteria in activated sludge: Geographic distribution and impact of treatment processes - Rui Liu; Yang Chen; Song-Ya Li; You-Peng Chen; Jin-Song Guo; Shao-Yang Liu; Peng Yan (Journal of Environmental Management, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Microwave-assisted synthesis and functionalization of biochar for environmental remediation: Regulate strategy and application potential - Jianhua Qu; Rui Yu; Xiaoyang Liu; Wei Peng; Fuxuan Bi; Xu Liu; Qiwen An; Yupeng Zhang; Qi Hu; Ying Zhang (Journal of Environmental Chemical Engineering, 2025)

Field test of geosynthetic-reinforced floating pile-supported embankments on soft soil - Rui Rui; Shi-kai He; Long-fan Peng; S.J.M. Van Eekelen; Liang-hao Li; Yu-qiu Ye (Geotextiles and Geomembranes, 2025)

High performance Ni-MgO (111) nanosheet catalysts for CO2 reforming with methane - Xirui Yan; Rui Wang; Fen Yue; Ruicong Wang; Huigang Zhang; Jun Li; Wencai Peng; Jinli Zhang (Fuel, 2025)

Lactic acid bacteria-mediated transformation of black tea extract: Insights into metabolite profile and sensory characteristics - Zhi-Peng Cheng; Yao-Zeng Zhang; Zhong-Zheng Guan; Rui-shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2025)

An alternative ignition agent concept based on ionic integrated energetic oxidant - Xiaoxia Li; Peng Ren; Rui Wu; Yu Wang; Peng Deng; Kehua Han; Yu Shang; Shaoli Chen; Weixiong Zhang (Chemical Engineering Journal, 2025)

Tanshinone IIA@β-cyclodextrin encapsulated with Eucommia ulmoides rubber/acetylated starch film as novel oral delivery system for therapy of orthotopic colon cancer - Rui Zhao; Haoyu Wang; Shuyao Li; Lingling Wang; Xiaopeng Lei; Pai Peng; Linlin Du; Juane Dong (Carbohydrate Polymers, 2025)

High-throughput screening method for glycolipids based on substrate modification and their efficient biomanufacturing - Yuanyi Li; Zhilin Liu; Yiming Zheng; Ke Sun; Peng Lei; Yian Gu; Yongting Song; Jian Xue; Weidong Cai; Rui Wang; Hong Xu; Liang Sun (Bioresource Technology, 2025)

Characterization and Assessment of Sheep-Origin Probiotic Bacillus licheniformis B63 Strain for Potential Use in Intestinal Health and Disease - Meng Hou; Yabin Lu; Mengjun Ye; Na Li; Yawei Sun; Gang Yao; Jinquan Wang; Fangfang Yin; Qimin Peng; Sheng Jia; Rui Shi; Xuxiang Wang (Probiotics and Antimicrobial Proteins, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Establishment of cell suspension culture and genetic transformation systems for production of bioactive metabolites of medicinal plant Artemisia argyi Lévl. et Vant - Yukun Li; Sainan Peng; Jingyi Zhang; Chuang Xiao; Rui Zhao; Yuhuan Miao; Dahui Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Microrna363-5p targets thrombospondin3 to regulate pathological cardiac remodeling - Yu-kun Ma; Xin-yi Han; Shu-huai Zan; Hui-ting Liu; Xue-yan Zhou; Dan-xue Zhao; Rui Xing; Peng Zhao (Molecular and Cellular Biochemistry, 2025)

Swertiamarin relieves radiation-induced intestinal injury by limiting DNA damage - Zhe Zhao; Dan He; Jinyu Wang; Yu Xiao; Lixin Gong; Can Tang; Haibo Peng; Xuemei Qiu; Rui Liu; Tao Zhang; Jingyi Li (Molecular and Cellular Biochemistry, 2025)

Research progress of non-coding RNA regulating the role of PANoptosis in diabetes mellitus and its complications - Guangyu Han; Kaibo Hu; Tianfeng Luo; Wenting Wang; Deju Zhang; Liu Ouyang; Xiao Liu; Jianping Liu; Yuting Wu; Jianqi Liang; Jitao Ling; Yixuan Chen; et al. (Apoptosis, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Reconstruction of well-logging data using unsupervised machine learning-based outlier detection techniques (UML-ODTs) under adverse drilling conditions - Jing-Rui Chen; Rui-Zhao Yang; Ting-Ting Li; Yun-Di Xu; Zhi-Peng Sun (Applied Geophysics, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Ultrasound-assisted extraction of flavonoids from Rudbeckia hirta L. flowers using deep eutectic solvents: Optimization, HPLC analysis and anti-inflammatory activity - Jiang-Rui Wang; Yin-Long Li; Hai-Tao Zhang; Zhao-Bao Xiang; Jing Zuo; Bo Peng; Xing-Yu Liu; Hong Ou (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Fruit wines classification enabled by combing machine learning with comprehensive volatiles profiles of GC-TOF/MS and GC-IMS - Changlin Zhou; Yashu Yu; Jingya Ai; Chuan Song; Zhiyong Cui; Quanlong Zhou; Shilong Zhao; Rui Huang; Zonghua Ao; Bowen Peng; Panpan Chen; Xiaoxiao Feng; et al. (Food Research International, 2025)

Exploration of the regulatory mechanism of pulsed electric field on the aggregation behavior of soybean protein isolates - Rui Wang; Pei-Feng Guo; Jin-Peng Yang; Yan-Yan Huang; Lang-Hong Wang; Jian Li; Song-Yi Lin; Qing-Lin Sheng; Xin-An Zeng; Yong-Xin Teng (Food Hydrocolloids, 2025)

Immune regulation differences in Large yellow croaker with varied resistance to Cryptocaryon irritans infection - Zhou Jiang; Ji Zhao; Rui Li; Qiaozhen Ke; Jiaying Wang; Yin Li; Shuimu Hu; Junjia Zeng; Fei Pu; Ning Li; Peng Xu; Tao Zhou (Fish & Shellfish Immunology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Unexplored role of nanoconfinement in regulating contaminant oxidation pathways for water decontamination: Confined energy driving low-carbon route - Min Tang; Wu Liu; Zhiyong Wang; Zhaoduan Hu; Jinquan Wan; Rui Peng (Chemical Engineering Journal, 2025)

Dual-targeting of PDPN-expressing synovial fibroblasts and macrophages via CLEC-2-engineered exosomes for osteoarthritis therapy - Bo Yu; Rui Peng; Zitao Liu; Shanchuang Chen; Nanjun Xu; Qingjun Yang; Zhengang Zha; Bolai Chen; Tao Jiang; Tao Gui; Songwei Huan (Chemical Engineering Journal, 2025)

Coplanar two-dimensional Cu-MOF with dual-Cu sites for electrocatalytic CO2 reduction to C2H4 - Yu-Peng Han; Zi-Rui Wang; Ya-Yu Yan; Qiao-Hong Li; Ping Shao; Hai-Xia Zhang; Li-Li Han; Fei Wang; Jian Zhang (Chemical Engineering Journal, 2025)

Enhanced electrochemical performance of NCM811-based batteries by using a multifunctional electrolyte additive - Aijia Wei; Shuxing Mei; Jinping Mu; Peng Liu; Xue Bai; Rui He; Xiaohui Li; Yuxin Niu; Lihui Zhang; Zhenfa Liu; Lei Wang (Chemical Engineering Journal, 2025)

Dynamics of soil phosphorus fractions during the early recovery stage of two typical plantations in China after strip clearcutting - Linhui Zhang; Jihong Li; Su Chen; Wenlan Huang; Lulu Huang; Hongfeng Zhu; Yuanxiang Tang; Han Li; Chengming You; Lixia Wang; Sining Liu; Hongwei Xu; et al. (CATENA, 2025)

Functional characterization and site-directed mutagenesis of a novel UDP-glycosyltransferase from Panax japonicus var. major - Lu Mou; Yang Zhang; Yu-Xin Zhuang; Rui-Fang Ren; Ran Xu; Ling Yang; Shao-Peng Zhang; Deng-Xiang Du (Planta, 2025)

Effect of Powdery Mildew Pathogen Inoculation on Gene Expression Levels and Root Microbial Community Structures in Bottle Gourd and Pumpkin Seedlings - Jian Zhang; Wen-Wen Wang; Peng-Cheng Wang; Rui Xia; Tong-Chun Gao (Journal of Soil Science and Plant Nutrition, 2025)

Metabolome analysis reveals the involvement of oxylipins in regulating the maturation of conchosporangia in Pyropia haitanensis - Yi Liu; Haike Qian; Shanshan Zhu; Tingting Niu; Qijun Luo; Juanjuan Chen; Rui Yang; Peng Zhang; Tiegan Wang; Haimin Chen (Algal Research, 2025)

Seismic Prediction Methods for Tidal Flat Sand Bodies in the Shunbei Area of the Tarim Basin - Zhi-peng Sun; Rui-zhao Yang; Jing-rui Chen; Hao Zhang; Shi-jie Zhang; Peng-hui Yang; Feng Geng (Applied Geophysics, 2025)

Deformation mechanism and treatment technology research of coal pillars in acute inclined goafs under expressway - Wei-Xing Bao; Zhi-Wei Ma; Hong-Peng Lai; Rui Chen (Applied Geophysics, 2025)

CircTBCK protects against osteoarthritis by regulating extracellular matrix and autophagy - Wei Wang; Yuzhe Sun; Peng Tang; Rui Zhang; Yufeng Jiang; Hongwei Min; Chen Gao (Human Cell, 2025)
Osteoarthritis (OA) is a widespread chronic bone and joint disease for which there is currently no effective preventive or therapeutic treatment. Accumulating evidence indicates that circular RNAs (circRNAs), a class of noncoding RNAs, play critical roles in OA. Therefore, in this study, we aimed to reveal an unexplored circTBCK and elucidate its mechanism of action in the pathological process of OA. The different expression of circTBCK was obtained both in vitro and in vivo. In the in vivo model, mice were induced via destabilization of the medial meniscus (DMM) surgery, while in vitro model, mouse cells like primary chondrocytes of newborn mice and ATDC5 cell line were treated with IL-1β treatment (10 ng/mL for 24 h). The level of circTBCK was examined by quantitative real-time polymerase chain reaction (qRT-PCR). After circTBCK was overexpressed or knocked down, IL-1β treatment was performed, and then, chondrocyte viability was detected via a Cell Counting Kit-8 (CCK-8) assay at 0, 24, 48, or 72 h. To assess type II collagen (Collagen II) expression, immunofluorescence (IF) analysis was used. The levels of mRNAs and proteins related to proliferation, the extracellular matrix (ECM) and autophagy were determined by qRT-PCR and Western blotting. Compared with OA treatment, primary chondrocytes with treatment of both circTBCK overexpression and IL-1βincreased the expression of anabolic factors—Collagen II and SRY-box transcription factor 9 (SOX9), proliferation-related molecules—Ki-67 and proliferating cell nuclear antigen (PCNA), and autophagy-related molecules—Microtubule-associated protein 1 light chain 3 (LC3), B-cell lymphoma 1 (Bcl1), and autophagy-related 5 (Atg5) and decreased Sequestosome 1 (SQSTM1 or P62). In contrast, knockdown of circTBCK aggravated the chondrocyte degeneration induced by IL-1β. Overall, our findings suggest that circTBCK, an unexplored circRNA, could regulate autophagy, proliferation, and the extracellular matrix (ECM) to mitigate the development of OA, suggesting a possible target for OA prevention and therapy.

Sequential decline in cyanobacterial, total prokaryotic, and eukaryotic responses to backward flow in a river connected to Lake Taihu - Jun Zuo; Siyu Yang; Hans-Peter Grossart; Peng Xiao; He Zhang; Rui Sun; Guoyou Li; Haoran Jiang; Qihang Zhao; Meng Jiao; Yao Cheng; Zeshuang Wang; et al. (Water Research, 2025)

Corrigendum to “Antiviral effects of duck type I and type III interferons against Duck Tembusu virus in vitro and in vivo” [Vet. Microbiol. 287 (2023) 109889] - Peng Zhou; Dejian Liu; Qingxiang Zhang; Wanrong Wu; Dong Chen; Rui Luo (Veterinary Microbiology, 2025)

Analysis of the city-scale wind environment and detection of ventilation corridors in high-density metropolitan areas based on CFD method - Rui Liu; Yuxiang Wang; Yu Zhang; Zhixing Peng; Hankai Chen; Xiang Li; Hang Li; Weiyue Li (Urban Climate, 2025)

A novel ensemble framework based on intelligent weight optimization and multi-model fusion for air quality index prediction - Shijie Qian; Tian Peng; Rui He; Jie Chen; Xuedong Zhang; Muhammad Shahzad Nazir; Chu Zhang (Urban Climate, 2025)

Equol promotes the in vitro maturation of porcine oocytes by activating the NRF2/KEAP1 signaling pathway - Sai Xiao; Ke Peng; Rui Chen; Xinxin Liu; Benliang Zhou; Rijing He; Yujun Yan; Runtian Wan; Ye-Shi Yin; Shengsheng Lu; Xingwei Liang (Theriogenology, 2025)

Niche and interspecific association of dominant zooplankton species near the Taishan coastal area in the South China Sea - Rui He; Bingqing Xiao; Ren Hu; Hongliang Tang; Jingxin Wei; Peng Wu (Marine Environmental Research, 2025)

Anammox sludge granulation and synergy with comammox: A critical review - Rui Zhao; Xiaonong Zhang; Da Jin; Xurui Zhu; Luomiao Ji; Bo Gao; Peng Wu (Journal of Environmental Chemical Engineering, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

Mechanical deformation destabilizing hydrate within thermodynamic equilibrium region - Peng Zhang; Xueping Chen; Rui Bao; Xu Ma; Yulu Wang; Yangli Che; Lianhai Zhang; Yingmei Wang; Jing Zhan; Guangjun Guo; Changyu Sun; Jianyang Wu; et al. (Fuel, 2025)

Microplastics and Dechlorane Plus co-exposure amplifies their impacts on soybean plant - Yu Xie; Junzhe Zhang; Yaping Lyu; Yaqi Jiang; Yi Sun; Ziqi Zhang; Haojie Wei; Xingxin Liu; Yukui Rui; Wenlong Yang; Peng Zhang (Environmental Pollution, 2025)

A review of emission characteristics and risk assessments of volatile organic compounds in petrochemical industry areas - Jinchan Peng; Yunxia Feng; Anshan Xiao; Bo Li; Dewu Ding; Guolong Wang; Rui Dong (Environmental Pollution, 2025)

Assessing seasonal thermal environment of two tree species: Integrating modeling and in-situ data in hot-summer and cold-winter climates - Hankai Chen; Rui Liu; Yuxiang Wang; Zhixing Peng (Building and Environment, 2025)

Associations of phthalate and phthalate alternative metabolites in urine with the risk of gallstones in adults: a cross-sectional analysis - Tianshan Shi; Di Li; Donghua Li; Peng Xie; Jin Sun; Tingrong Wang; Rui Li; Zixuan Zou; Zhenjuan Li; Xiaowei Ren (Environmental Geochemistry and Health, 2025)

Factors governing bark tufa deposition in fluvial systems: the case study of Nuorilang in Jiuzhaigou, Sichuan China - JunHao Li; FuDong Wang; WuYang He; QinYingZi Cai; Shi Chen; GuoQing Huang; Dawood Muhammad; Carlos Pérez-Mejías; Rui Zhang; ZiTong Peng; SiRui Chen; ChenWei Ji; et al. (Carbonates and Evaporites, 2025)

Association Between Exposure to Multiple Toxic Metals in Follicular Fluid and the Risk of PCOS Among Infertile Women: The Mediating Effect of Metabolic Markers - Xin Wang; Ying Zhang; Jie Peng; Hua Zhang; Tingting Jiang; Zhikang Zhang; Tao Yin; Xun Su; Tao Zhang; Lingchao Shen; Shitao He; Xiaolei Wang; et al. (Biological Trace Element Research, 2025)

The extensive cultivation of Pyropia haitanensis along the coastal areas influences the ecological dynamics of nearby intertidal mudflat pond water - Peihao Liu; Qijun Luo; Shanshan Zhu; Juanjuan Chen; Rui Yang; Tingting Niu; Tiegan Wang; Peng Zhang; Haimin Chen (Frontiers in Marine Science, 2025)
Introduction The aquaculture in intertidal mudflat ponds on the coast of the East China Sea typically coexists with oceanic seaweed cultivation in the nearby open water area, forming an interconnected aquatic ecosystem. This study aimed to understand the impact of the seaweed cultivation on the water quality and microbial communities in their neighboring intertidal mudflat ponds. Methods A unique recirculating culture system was established, integrating seaweed farming in marine areas with aquaculture ponds on mudflats, and incorporating an effluent treatment process for added efficiency. Water samples were collected from three sites, including open water areas with or without seaweed ( Pyropia haitanensis ) cultivation, the aquaculture mudflat ponds, and effluent water ponds, with control sites for comparison. The dynamic diversity patterns and structure of microbial communities were determined by 16S and 18S rRNA sequencing, and the environmental factors were measured. Results In the offshore aquaculture area, the cultivation of P. haitanensis increased the dissolved oxygen and pH, decreased inorganic nutrients, reduced the alpha diversity of bacteria, established the dominance of Proteobacteria, but did not influence the composition of microeukaryotes. These changes in the seawater subsequently affected the dynamics in the corresponding aquaculture ponds, where the water quality was improved, the microbial diversity was enhanced, and the abundance of functional bacteria such as Microbacteriaceae was increased. According to the co-occurrence network analysis, the cultivation of P. haitanensis potentially improved the stability of the microbial communities in both the offshore aquaculture area and the onshore aquaculture ponds and allowed them to resist stress better. In addition, after the effluent from the aquaculture ponds was purified in the treatment ponds with mangroves and oysters, the water quality improved and the abundances of Dinophyceae and Bacillariophyta decreased. Discussion This study highlights the positive effects of P. haitanensis cultivation on water quality and microbial stability in adjacent aquaculture ponds.

Ecological economic resilience in China: systematic performances, structural characteristics and evolutionary predictions - Kexin Wang; Rui Ding; Wenqian Xiao; Juan Liang; Lina Peng; Shuyue Jiang (Environment, Development and Sustainability, 2025)

Underwater Target Detection with High Accuracy and Speed Based on YOLOv10 - Zhengliang Hu; Le Cheng; Shui Yu; Pan Xu; Peng Zhang; Rui Tian; Jingqi Han (Journal of Marine Science and Engineering, 2025)
Underwater target detection exhibits extensive applications in marine target exploration and marine environmental monitoring. However, conventional images of underwater targets present challenges including blurred contour information, complex environmental conditions, and pronounced scattering effects. In this work, an underwater target detection method based on YOLOv10 is designed, and the detection performance is compared with the YOLOv5 model. Experimental results demonstrate that the YOLOv10 model has a mAP50 of 85.6% on the URPC 2020 dataset, improving the mAP50 by 1.2% than that of YOLOv5. This model exhibits high detection accuracy and high proceeding speed, which provides a promising support for precise and fast underwater target detection.

Community Dynamics of Fish Larvae in Coastal Zhejiang: Seasonal Variations in Spatiotemporal Distribution and Environmental Driving Factors - Peng Zhao; Rijin Jiang; Qiqun Li; Rui Yin; Yuelian He; Qingxi Han; Guangjie Fang (Fishes, 2025)
The coastal waters of Zhejiang feature a complex aquatic environment and abundant biological resources, creating an ideal habitat for various fish species. However, the systematic monitoring of fish larvae in these offshore waters is limited. This study collected 24,232 fish larvae using large plankton nets during April and November 2022, as well as February and July 2023, and identified 93 species, primarily warm-temperate and warm-water species, with a peak occurrence in summer. The dominant species include Larimichthys croceus, Sebastiscus marmoratus, Lateolabrax japonicus, and Odontamblyopus lacepedii, among others, and these species exhibit frequent seasonal changes. Fish larvae are typically found to be aggregated along estuaries and bays in spring, autumn, and summer, while in winter, they tend to shift towards areas near the boundaries of motor trawler fisheries areas. Our cluster analysis revealed spatial heterogeneity in the community structure, driven by an abundance of dominant and important species. Our Mantel tests and canonical correspondence analysis (CCA) identified seawater temperature and salinity as core drivers of the aggregation and distribution of fish larvae, interacting with factors such as the chlorophyll-a concentration, water turbidity, water depth, and dissolved oxygen. This research provides a scientific basis for the dynamic monitoring of spawning grounds and effective management of fishery resources in Zhejiang’s coastal waters.

Renewable energy investment under carbon trading mechanism: the impact of green financing and carbon emission quota - Jun Wang; Weicai Peng; Chenhao Ke; Zhongzhi Wang; Shitao Zhang; Zhaobiao Rui; Xiaomeng Shi (Environment, Development and Sustainability, 2025)

Toward safe rice production in As-Cd co-contaminated paddy soils: Biogeochemical mechanisms and remediation strategies - Jing-Min Yang; Hui-Lin Chen; Xin Wang; Dong-Xing Guan; Xiong-Hui Ji; Yun-He Xie; Rui Huang; Bo Peng; Qin-Bo Qin (Critical Reviews in Environmental Science and Technology, 2025)

Migration modeling of metal(loid)s in soil-groundwater systems from an abandoned mine: Based on multimethod integration - Chiyue Huang; Zhaohui Guo; Rui Xu; Chi Peng (Science of The Total Environment, 2025)

Phylogenomic analyses of hamsters (Cricetinae) inferred from GBS data and mitochondrial genomes - Xuan Pan; Xuming Wang; Yingxun Liu; Yuchun Li; Rui Liao; Zhongzheng Chen; Buqing Peng; Xichao Zhu; Jiatang Li; Shaoying Liu (Molecular Phylogenetics and Evolution, 2025)

Microbial mechanisms of sulfate reduction for low-temperature bioremediation of acid-mined uranium sandstone groundwater - Rui Xiao; Zhenghua Liu; Min Xu; Guoping Jiang; Yang Peng; Cunzeng Li; Jie Wang; Huaqun Yin; Lechang Xu (Journal of Water Process Engineering, 2025)

Drivers of ecological drought recovery: Insights from meteorological and soil drought impact - Chenhao Ge; Peng Sun; Rui Yao; Yayi Zhang; Han Shen; Huilin Yang (Journal of Hydrology, 2025)

Study on the evolution of ecological flow in river and its guarantee degree during different hydrological periods - Xue Chen; Qin Li; Zhuo Jia; Rui Xiao; Zhijin Cheng; Yuhao Peng (Journal of Cleaner Production, 2025)

Exploring the freshness biomarker and volatiles formation in stored pork by means of lipidomics and volatilomics - Yuping Zhang; Jingyu Li; Zixu Zeng; Xiangru Wei; Nigel P. Brunton; Yanqing Yang; Peng Gao; Jiangtao Xing; Pi Li; Fangjie Liu; Rui Liu; Qianqian Li; et al. (Food Research International, 2025)

Monoclonal antibody-based lateral flow immunoassay:An alternative solution for the rapid detection of formaldehyde - Lin Luo; Rui Liang; Zhan-Peng Chen; Bao-Zhu Jia; Ai-Fen Ou; Rong-Rong Zhan; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu (Food Bioscience, 2025)

Differential accumulation of bioactive compounds in different populations of Mesona chinensis Benth: An integrated transcriptomic and metabolomic analysis - Yan Qin; Rui Xie; Shirui Peng; Guoming Yang; Xiaomu Yang; Zihao Long; Ying Zheng; Guoli Ye; Minghua Gu; Yanyan Wei (Food Bioscience, 2025)

Poly-γ-glutamic acid chelates chromium (III) and copper (II), alleviating their toxicity in cucumber and affecting rhizosphere bacterial community assembly - Chaoyang Chen; Wenhui Yan; Yu Chen; Sijie Liu; Chuanjiang Nong; Liang Sun; Rui Wang; Hong Xu; Peng Lei; Yian Gu (Environmental Pollution, 2025)

Programmable allosteric DNA nanomachine for ratiometric imaging of VEGF in tumor cells - Jia-Wei Liang; Yan-Mei Lei; Zhao-Peng Chen; Xue-Mei Zhou; Ya-Qin Chai; Ruo Yuan; Rui Du; Ying Zhuo (Chemical Engineering Journal, 2025)

Laser-induced ZnxMnOx-rGO-C@LIG materials doped with diesel distillate for Zn-ion hybrid supercapacitors - Yuxia Wang; Hu Zou; Zhong Qi; Siyu Yang; Wenlong Jiang; Rui Zhang; Zhengchun Yang; Junjun Shi; Jie He; Peng Pan; Huayi Li (Chemical Engineering Journal, 2025)

Water-triggered stimuli-responsive luminescent crown-ether-coordinated cuprous bromides for multi-functional applications - Rui Wu; Hao Yang; Meifeng Jiang; Hui Tong; Xinyu Hu; Ziyang Liu; Chunhua Luo; Hui Peng; Hechun Lin (Chemical Engineering Journal, 2025)

Visible light-powered photodynamic antibacterial chlorophyllin-derived metallochlorins - Yuling Xue; Kuoran Xing; Max Jing Rui Tham; Bang Lin Li; Narattam Sikdar; Lai Peng Leong; Ching Hua Lee; Justin Jang Hann Chu; Wee Han Ang; David Tai Leong (Chemical Engineering Journal, 2025)

ε-Poly-L-lysine/rhamnolipid bifunctional coating based on green electrostatic assembly technology for fruit packaging and preservation - Quanfei Li; Qian Chen; Kai Yang; Hao Liu; Delei Xu; Yian Gu; Liang Sun; Peng Lei; Rui Wang; Hong Xu (Chemical Engineering Journal, 2025)

Development of a Novel TBM Tunnelling Test Platform and Its Application in Rock–Machine Interaction Analysis - Wei-Qiang Xie; Xiao-Li Liu; Rui-Peng Qian; Jian Chen; En-Zhi Wang; Wei Hong (Rock Mechanics and Rock Engineering, 2025)

Intercropping: ecosystem functioning and sustainable agriculture - Rui-Peng Yu; Dorte B. Dresbøll; Maria R. Finckh; Eric Justes; Wopke van der Werf; Andrew Fletcher; Georg Carlsson; Long Li (Plant and Soil, 2025)

A rapid increase of groundwater in 2021 over the North China Plain from GPS and GRACE observations - Rui Zhang; Yujie Peng; Nengfang Chao; Qi Ou; Gang Chen; Zhengtao Wang; Hong Zhu; Bing Liu; Zixin Zhang (GPS Solutions, 2025)